2019
DOI: 10.3390/recycling4020018
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for the Use of Post-Processing Vacuum Bags from Aerospace Supplies: Nucleating Agent to LLDPE Phase in PA6/LLDPE Blends

Abstract: In the aerospace industry, many composite parts are manufactured by processes using plastic vacuum bags made of polyamide 6 (PA6) as a consumable material. This implies that after demolding the part, this plastic material should be discarded, generating a considerable amount of waste. Tons of vacuum bags are discarded and incinerated per month by several companies in this sector, which highlights the need to recycle and/or reuse this material. PA6/linear low-density polyethylene (LLDPE) blends are of great tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The fact that no other characteristic peaks were visible in the spectra confirmed the purity of recycled material, indicating that no other chemical reaction has occurred during the recycling process and no contamination exists inside the material. 39,40 T A B L E 1 The blown film compositions. These parameters include temperature, shear, and oxidation levels, leading to competitive and simultaneous chain scission and crosslinking phenomena.…”
Section: Ftir Characterization Of Virgin and Recycled Ldpe And Lldpementioning
confidence: 99%
“…The fact that no other characteristic peaks were visible in the spectra confirmed the purity of recycled material, indicating that no other chemical reaction has occurred during the recycling process and no contamination exists inside the material. 39,40 T A B L E 1 The blown film compositions. These parameters include temperature, shear, and oxidation levels, leading to competitive and simultaneous chain scission and crosslinking phenomena.…”
Section: Ftir Characterization Of Virgin and Recycled Ldpe And Lldpementioning
confidence: 99%
“…According to the authors, it was possible to verify the feasibility of recycling end-of-life multi-material polymeric products to replace neat polymers such as PU. The study by Souza et al [93] used vacuum bags of PA6 discarded after the curing process in an autoclave in the aerospace sector to produce PA6/LLDPE (linear low-density polyethylene) blends. According to the authors, this process demonstrated a new strategy for PA6 recycling, contributing to the reduction of waste from the aerospace industry.…”
Section: Pa Recycling Processesmentioning
confidence: 99%
“…8,9 The growing demand for high-performance materials combined with the reduction of CO 2 emissions and, consequently, the need to reduce the structural weight of vehicles caused the global CFRP market to present annual growth of 6%. It was estimated that in 2025 the annual consumption would reach $27 billion, 10,11 already estimating a drop in 2020 and 2021 due to the global economic recession led by the pandemic (COVID- 19). This means, consequently, an increase in the demand for carbon fiber (CF) of approximately $2.8 billion by 2025 to obtain the CFRP and estimated demand of approximately 194 kt for CFRP in 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it can be cited the reuse and recycling to reduce the disposal of waste destined for landfills and/or incineration, such as prepreg scraps, 15,16 protective prepreg packages, 17,18 and post-processing vacuum bags. 19 In addition to generating tailings from the production system, product residues, after their useful life, such as aircraft and automobiles, need to be properly disposed of. [20][21][22] In the aerospace sector, it is estimated that by 2050 all companies and suppliers will propose a system aimed at the reuse, remanufacturing, and recycling of their products at their Endof-Life (EoL) through the development of economically sustainable techniques and disposal management for CFRPs to obtain a circular economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation